Analisis Model Digital Forensic Readiness Index (Difri) Terhadap Serangan Malware - Yogi Pratama; Ramdhani Syahputra (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The increasing number of malware spread in the world today, then there will be more opportunities to commit crime, so readiness is needed for every internet user in dealing with these crimes. The readiness to handle crime is called digital forensic readiness. Therefore, we need a specific digital forensic readiness model to measure the level of readiness of internet users or institutions in achieving malware attacks. This model has the main components used to determine or calculate the level of readiness of internet users or institutions, the main components are the strategy component, the policy & procedure component, the technology & security component, the digital forensic response component, the control & legality component. The calculation method used in this study is a Likert Scale, with this method the results will be obtained that are closer to the real situation. The value / index of readiness level obtained will provide recommendations to internet users and these recommendations can be used to make improvements properly and on target.